To be SEER 1.0 or not to be SEER 2.0? That is one of a few questions - Cruz, Isabel CF da (Online Brazilian Journal of Nursing, 2007)
The intent of this editorial is to share the fears related to the migration to a new version of the OJS/PKP and to highlight the strengths of the OBJN with the use of the OJS. The editorial also poits out many questions related to the contribuition of the OBJN to the scholars as well as quastions that includ the critical issues of time, costs, and planning.